NILAI KEARIFAN UNGKAPAN BUDAYA JAWA “RUKUN AGAWE SANTOSA” DALAM GAGASAN PEMIKIRAN EMMANUEL LEVINAS - Theresia Pratiwiningsih (Universitas Hasanuddin, 2020)
The focus of this research is the theme of Javanese local wisdom culture which related to Javanese proverb expressions about